2005
DOI: 10.1016/j.jom.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Market priorities, manufacturing configuration, and business performance: an empirical analysis of the order‐winners framework

Abstract: This study carries out an empirical test of the order-winners framework in manufacturing organizations. Hill [Hill, T., 1985. Manufacturing Strategy: The Strategic Management of the Manufacturing Function, first ed. Macmillan, Basingstoke; Hill, T., 2000. Manufacturing Strategy: Text and Cases, second ed. Palgrave, Basingstoke] proposed the order-winners framework to help managers to improve understanding about markets and to develop a consistent manufacturing strategy. The framework defines ideal profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 37 publications
1
63
0
2
Order By: Relevance
“…Different studies have contrasted these theoretical issues, supporting the thesis that the structural characteristics of the environment condition the success of the business strategies (Anderson & Zeithaml, 1984;Hambrick, 1983;Hambrick, MacMillan, & Day, 1982;Lenz, 1980;Miller, 1987;Tan & Tan, 2005;Silveira, 2005;Murillo-Luna, Garcés-Ayerbe, & Rivera-Torres, 2008;Nadkarni & Barr, 2008;Woo & Cooper, 1982). Lenz (1980) asserts that the combination of environment, strategy and organizational structure for firms with high performance is significantly different from that associated with firms with low performance.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 96%
“…Different studies have contrasted these theoretical issues, supporting the thesis that the structural characteristics of the environment condition the success of the business strategies (Anderson & Zeithaml, 1984;Hambrick, 1983;Hambrick, MacMillan, & Day, 1982;Lenz, 1980;Miller, 1987;Tan & Tan, 2005;Silveira, 2005;Murillo-Luna, Garcés-Ayerbe, & Rivera-Torres, 2008;Nadkarni & Barr, 2008;Woo & Cooper, 1982). Lenz (1980) asserts that the combination of environment, strategy and organizational structure for firms with high performance is significantly different from that associated with firms with low performance.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 96%
“…In doing so, this paper addresses the current gap within the literature around the lack of research into internal strategic fit in service organisations. It also meets the need for a more focused, in-depth investigation into fit (Menda and Ditts, 1997;Meredith, 1998, Boyer et al, 2005and Sousa and Voss, 2008) and further approaches, concepts and guidelines for analysing and testing it (da Silveira, 2005;Santala and Parvinen, 2007).…”
Section: Insert Table 1 Around Herementioning
confidence: 97%
“…DeRuntz and Turner (2003) found that careful selection of management practices was conducive to AMT success. Given the high cost of AMT and the importance that such investments have on firm performance (Da Silveira, 2005), it is vital to understand the impact that management practices have on success. The literature on the nature of technology implementation uses two primary modes of analysis -technology adoption/diffusion and complementarities between technologies.…”
Section: Introductionmentioning
confidence: 99%